2006
DOI: 10.1007/s11103-006-9027-9
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of chloroplast HSP100/ClpB in the acquired thermotolerance in tomato

Abstract: The chloroplast HSP100/ClpB is a newly documented member of the ClpB family, but little was known about its role in imparting thermotolerance to cells. A cDNA coding for a HSP100/ClpB homolog has been cloned from Lycopersicon esculentum and termed as Lehsp100/ClpB (the cDNA sequence of Lehsp100/ClpB has been submitted to the GenBank database under accession number: AB219939). The protein encoded by the cDNA was most similar to the putative chloroplast HSP100/ClpBs in higher plants and the ClpB from Cyanobacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 41 publications
1
59
0
Order By: Relevance
“…[See online article for color version of this figure.] Katiyar-Agarwal et al, 2003). Cytosolic Hsp70 and plastid ClpB and small heat shock proteins have also been implicated in heat sensitivity of plants (Lee and Schö ffl, 1996;Sung and Guy, 2003;Wang and Luthe, 2003;Miroshnichenko et al, 2005;Myouga et al, 2006;Yang et al, 2006;Lee et al, 2007). However, no such role has been proposed for plastid Hsp70s.…”
Section: Discussionmentioning
confidence: 99%
“…[See online article for color version of this figure.] Katiyar-Agarwal et al, 2003). Cytosolic Hsp70 and plastid ClpB and small heat shock proteins have also been implicated in heat sensitivity of plants (Lee and Schö ffl, 1996;Sung and Guy, 2003;Wang and Luthe, 2003;Miroshnichenko et al, 2005;Myouga et al, 2006;Yang et al, 2006;Lee et al, 2007). However, no such role has been proposed for plastid Hsp70s.…”
Section: Discussionmentioning
confidence: 99%
“…In plants, heat shock (HS) affects growth and crop production. Most organisms, including higher plants, synthesize heat shock proteins (HSPs) in response to high-temperature stress (Vierling, 1991;Queitsch et al, 2000;Nieto-Sotelo et al, 2002;Charng et al, 2006;Yang et al, 2006). In eukaryotes, expression of HSPs is regulated by heat shock transcription factors (HSFs).…”
mentioning
confidence: 99%
“…Tomato ClpB/ Hsp100-c was found to be heat shock induced (Yang et al 2006). Gulli et al (2007) reported that four Hsp100 gene transcripts behaved in different manner with respect to each other in response to heat stress in T. durum.…”
Section: Plant Clpc and Clpd Atpasesmentioning
confidence: 99%
“…It was further seen that the overexpression of apg6 inhibited chloroplast development, resulting in a mild pale green phenotype. Yang et al (2006) noted that tomato plants in which expression of chloroplastic ClpB/Hsp100 (ClpB/Hsp100-c) was repressed by an antisense construct, show high temperature sensitivity. Mutant plants in the latter work showed enhanced irreversible thermal inactivation of PSII to high temperature stress.…”
Section: Probable Cellular Functions Of Plant Clpb/hsp100 Proteinsmentioning
confidence: 99%